Improving outcomes for looked after children - Horsburgh, Jacqui (Emerald Publishing Limited, 2022)
Providing support for practitioners and leaders at all levels in education, this book discusses why there is a need to rethink how we provide support for looked after children and young people in a positive way that will encourage a path into education, training, or employment when they leave school. Horsburgh presents case studies based on interviews with looked after children of primary school age, their carers, teachers, and support staff. Each study illustrates aspects of the social context within which looked after children were supported and presents examples of each child's experience of learning, drawn from discussions with staff and children. This is merged with evidence from observation to compile each profile. These provide the reader with a vicarious account of the looked after children's experience of school and the different ways in which they are supported to engage in learning. Reflective questions and audit tasks accompany the case studies to support practitioners in reviewing and improving the support that they provide for looked after children and their carers.
Keywords: Student assistance programs.; Children -- Institutional care.; Education, Elementary.; Inclusive education.; Education -- Special Education -- General.; Teaching of specific groups & persons with special educational needs.; elektronické knihy; electronic books